Health Criminal Law as an Instrument to Protect Human Rights: A Comparative Study of Indonesia and Algeria - Wirya Darma, I Made; Mahadnyani, Tjokorda Mirah Ary; Agus Kurniawan, I Gede; Driss, Bakhouya (Universitas Negeri Surabaya, 2025)
Health criminal law in the Indonesian context is actually regulated in Article 427 to Article 448 in Law 17 of 2023 concerning Health (Health Law). This is a major change in the health sector and covers various aspects that regulate public health, health services, and criminal law related to violations in the health sector. This study aims to analyze two important aspects, namely: (i) the regulation of health criminal law between Indonesia and Algeria and its relation to the protection of human rights, and (ii) the future regulation of health criminal law in Indonesia in realizing the protection of health rights for the community. This research is a normative legal research with conceptual, comparative and legislative approaches. The result of the research confirms that health criminal law can be said to be the main instrument to maintain and ensure health rights for the community. The findings of this research confirm that the main difference between Indonesia and Algeria lies in the way health criminal law is organized and applied. Indonesia has more detailed and specific regulations that address malpractice, medical negligence and the health sector more holistically. Whereas Algeria tends to regulate this in a more general framework, following the existing criminal code. The recommendation from this study is that there is a need for legal harmonization between health criminal sanctions in Articles 427 to 448 in Law 17 of 2023 on Health (Health Law) and the New Criminal Code including more detailed special regulations on malpractice, including investigation procedures, evidence, and criminal sanctions against medical personnel who are proven to be negligent or deliberately commit medical errors. This will provide legal certainty for patients and medical personnel.